Do ICT boost business-to-business satisfaction in times of uncertainty? - Gil-Saura, Irene; Berenguer-Contri, Gloria; Ruiz-Molina, María-Eugenia; Gil-Saura, Roberto; Juma-Michilena, Israel-Javier (Journal of Business Economics and Management, 2025)
Tourism is a highly sensitive industry concerned about the social and economic consequences of instability. In this sense, it is vital to understand how relationships develop and what factors lead to satisfaction among the stakeholders. Most research on tourism has focused on analysing B2C relationships, but B2B relationships have been considerably neglected. This paper aims to test whether theoretical relationships postulated in a B2C setting are transferable to the B2B environment. A novel model is postulated to explain the factors that lead to satisfaction among tourism businesses by considering technology, customer orientation, sustainability, and brand equity as key antecedents for social and economic satisfaction in B2B relations. Data from 268 managers of Spanish hotels were collected through a survey. The results obtained through partial least squares regression show that all but one of the hypotheses proposed in the model are supported, so that technology fosters both customer orientation and sustainability. Moreover, the chain customer orientation-brand equity-sustainability-social satisfaction-economic satisfaction, and therefore, this work contributes to understanding the elements that boost economic satisfaction in the relationships between hotels and travel agencies, and provides recommendations on the efficient use of technology.